2021
DOI: 10.3390/jcm10122599
|View full text |Cite
|
Sign up to set email alerts
|

Is It the Surgeon, the Patient, or the Device? A Comprehensive Clinical and Radiological Evaluation of Factors Influencing Patient Satisfaction in 648 Total Knee Arthroplasties

Abstract: Total knee arthroplasty (TKA) is a successful and safe surgical procedure for treating osteoarthritic knees, but despite the overall good results, some patients remain dissatisfied. The aim of this study is to evaluate the influence of patient-related and surgery-related variables in a consecutive group of patients that underwent TKA. Individuals (n = 648) who had TKA performed between 01 January 2013 and 31 December 2017 were enrolled in the study. Postoperative Western Ontario and McMaster Universities Osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Smoking status, which was a significant predictor of patient satisfaction in the current analysis, has rarely been assessed so far in this context. Only two studies examining the impact of smoking on patient satisfaction were found [45,46]. Rissolio et al assessed long-term outcomes of TKA (minimum follow-up: 24 months) and reported no association between smoking and surgery outcome satisfaction [45].…”
Section: Patient Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Smoking status, which was a significant predictor of patient satisfaction in the current analysis, has rarely been assessed so far in this context. Only two studies examining the impact of smoking on patient satisfaction were found [45,46]. Rissolio et al assessed long-term outcomes of TKA (minimum follow-up: 24 months) and reported no association between smoking and surgery outcome satisfaction [45].…”
Section: Patient Satisfactionmentioning
confidence: 99%
“…Only two studies examining the impact of smoking on patient satisfaction were found [45,46]. Rissolio et al assessed long-term outcomes of TKA (minimum follow-up: 24 months) and reported no association between smoking and surgery outcome satisfaction [45]. Halawi et al, however, who assessed patient satisfaction six and 12 months after TKA, found smokers to be less satisfied versus non-smokers (82% vs. 89%, p = 0.052) -independent of their psychological health status [46].…”
Section: Patient Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference is in line with other studies [ 12 , 13 ]. Furthermore, women demonstrated poorer clinical outcomes and lower satisfaction after surgery [ 14 , 15 ]. The gender difference has also been analyzed in other reviews, concluding that women are at increased risk for developing more severe postoperative pain conditions and subsequent CSPS [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have attempted to identify factors driving this high dissatisfaction rate. There is growing evidence that unfulfilled preoperative expectations are important determinants of patients’ dissatisfaction with TKA [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%